Tinjauan Kriminologis Terhadap Descructive Fishing dalam Penangkapan Ikan di Wilayah Perairan Pulau Kodingareng (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to identify and analyze the criminogenic factors that contribute to destructive fishing practices in the waters of Kodingareng Island, as well as to examine the strategies used to address this issue. The research employs an empirical approach by collecting primary data from investigators of the South Sulawesi Marine and Air Police Unit, offenders, and local communities, along with secondary data consisting of relevant legislation and previous studies. The findings show that most fishers work as papekang, papattek, and pagae, with highly unstable income levels. Patron–client relationships between punggawa, juragan, and pagae place fishers under significant production pressure, while access to explosives and mainland supply networks remains readily available. Perceptions of low legal risk due to limited maritime patrols, combined with maritime work values and cultural interpretations of the sea as a livelihood space, reinforce these practices within certain groups. Efforts to combat destructive fishing are ineffective when relying solely on law enforcement. Strengthened patrols, improved evidentiary processes, and enhanced inter-agency coordination must be integrated with non-penal strategies such as economic empowerment, accessible capital, environmental education, and community-based social capital reinforcement. Synergy between penal and non-penal policies provides a foundation better aligned with the social dynamics and geographical characteristics of Kodingareng.